Hipotesis Penelitian Kuantitatif - Yam, Jim Hoy; Taufik, Ruhiyat (Perspektif : Jurnal Ilmu Administrasi, 2021)
The objective of this paper is to discuss the understanding of hypothesis writing, by reviewing some related literature. Hypothesis is an important part of research, which needs to be designed from the beginning of the study. Since the hypothesis is a temporary answer to a research question, which is expected to guide the research’s path. So that it requires an in-depth understanding of the meaning and types of directional and non-directional hypotheses, as well as the application of 1 tailed and 2 tailed t-test techniques. At the eventually, There are 3 conclusions, are the written hypothesis can be expressed in 3 forms, consists of positively directional, negatively directional and non-directional. Keywords: Hypothesis, t test, quantitative research